2022
DOI: 10.1002/jcb.30280
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐spectrum cytotoxicity to cancer cells of Brevilaterin C from Brevibacillus laterosporus and its specific mechanism on human epidermal cancer cells

Abstract: Antimicrobial peptides (AMP) from Brevibacillus laterosporus have good prospects as clinical treatments for cancer. Nevertheless, details about their anticancer spectrum and mode of cytotoxicity remain poorly understood. A newly found AMP (named Brevilaterin C) secreted by B. laterosporus S62-9 exhibited strong inhibition on almost cancer cell lines examined at a concentration of 8 µg/ml but was relatively safe for normal cells. We further systematically examined its cytotoxicity and mechanism toward human epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In this study, we aimed to investigate the impact of BB/BC, a spectrum anticancer peptide [ 14 , 15 ], on gastric cancer cells. Our results showed that BB/BC strongly inhibited cell proliferation in a dose-dependent manner ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we aimed to investigate the impact of BB/BC, a spectrum anticancer peptide [ 14 , 15 ], on gastric cancer cells. Our results showed that BB/BC strongly inhibited cell proliferation in a dose-dependent manner ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cell lines tested in this study included BGC-823 gastric cancer cells and its corresponding gastric epithelial cell GES-1, which is a human normal cell. BGC-823 and GES-1 cell lines were cultured using RPMI 1640 medium supplemented with 10% FBS and 1% penicillin-streptomycin cocktail, and cultured at 37 °C in a humidified atmosphere containing 5% CO 2 , as described previously [ 14 ]. FBS, penicillin, and cultural media were all purchased from Gibco (Oklahoma, ME, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations